ENHANCING VOCABULARY LEARNING IN ELEMENTARY LANGUAGE EDUCATION: EXPLORING EFFECTIVE STRATEGIES AND INTERACTIVE APPROACHES - Joy Edilaine R. Handig ,Ace M. San Gabriel, Ricky Boy M. Garcia, Marinelle S. Domingo (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study delves into the instructional strategies employed by elementary language teachers for vocabulary teaching. Through in-depth interviews with five experienced educators, their approaches, challenges, and insights concerning vocabulary development were closely examined. The findings underscore the pivotal role of intentional and continuous word exposure in effective vocabulary instruction. The study identifies various strategies encompassing captivating games, collaborative group activities, visual aids such as graphic organizers, images, and labels, alongside consistent repetition of word sets. These techniques collectively bolster reading comprehension, writing proficiency, and oral communication skills among young learners. The research underscores the significance of cultivating dynamic and interactive learning settings that facilitate meaningful and consistent encounters with new vocabulary. The insights gleaned from this investigation contribute to the ongoing endeavor of refining vocabulary instruction methods, with the ultimate aim of fostering academic achievement and language progression in students. The study advocates for further exploration and application of these strategies to fully harness the benefits of vocabulary exposure in language teaching and learning.